Formation of Arabidopsis Cryptochrome 2 Photobodies in Mammalian Nuclei: APPLICATION AS AN OPTOGENETIC DNA DAMAGE CHECKPOINT SWITCH - Ozkan-Dagliyan, Irem (American Society for Biochemistry and Molecular Biology, 2013)
Nuclear bodies are discrete suborganelle structures that perform specialized functions in eukaryotic cells. In plant cells, light can induce de novo formation of nuclear bodies called photobodies (PBs) composed of the photosensory pigments, phytochrome (PHY) or cryptochrome (CRY). The mechanisms of formation, the exact compositions, and the functions of plant PBs are not known. Here, we have expressed Arabidopsis CRY2 (AtCRY2) in mammalian cells and analyzed its fate after blue light exposure to understand the requirements for PB formation, the functions of PBs, and their potential use in cell biology. We found that light efficiently induces AtCRY2-PB formation in mammalian cells, indicating that, other than AtCRY2, no plant-specific proteins or nucleic acids are required for AtCRY2-PB formation. Irradiation of AtCRY2 led to its degradation; however, degradation was not dependent upon photobody formation. Furthermore, we found that AtCRY2 photobody formation is associated with light-stimulated interaction with mammalian COP1 E3 ligase. Finally, we demonstrate that by fusing AtCRY2 to the TopBP1 DNA damage checkpoint protein, light-induced AtCRY2 PBs can be used to activate DNA damage signaling pathway in the absence of DNA damage.